Conceptual Design and Implementation of Geographic Information System (GIS) for Hutan Simpan Ayer Hitam, Selangor - Abdul Malek, Ismail Adnan (Universiti Putra Malaysia Press, 1999)
Geographic Information System (GIS) has created a large field of opportunity for the development of new approaches to computer processing of spatial or geographically referenced data, hence adding a new dimension to the management, analysis, and presentation of the large volumes of information required in the decision making processes. A GIS is proposed to be used for automation and analysis of data in the management of forest resources at Hutan Simpan Ayer Hitam, Puchong, Selangor. In addition to basic attribute and spatial query operations in the GIS, spatial modeling and surface analysis methods should also be used to assist forest planning and management at Ayer Hitam.